Evolution of seismicity at Kiruna Mine - Dineva, Savka; Boskovic, Mirjana (Luleå tekniska universitet, Geoteknologi, 2017)
Kiirunavaara (Kiruna) iron ore mine owned by LKAB (Sweden) is one of the largest underground mines. Miningstarted in 1898 as an open pit mine. In mid-1950, the mine started a transition to underground mining andpassed to only underground mining in 1962. More substantial problems with seismicity started in 2007-2008when the deepest mining level was 907 m (ca. 670 m below surface). By 2016, the mining production is at1,022–1,079 m Level (ca. 785–845 m below surface). More than one billion tonnes of ore have been extractedsince the beginning of mining. The average yearly production in recent years is 28 million tonnes.By 2016 the mine has the largest underground seismic system in the world with 204 operational geophones.The number of the sensors (geophones with natural frequencies of 4.5, 14, and a few of 30 Hz) changed withthe increasing of production depth. The major stages with seismic system upgrades are: August 2008–June2009 with 112 installed geophones, and July 2012–September 2013 with 95 installed geophones. During2016–2017 it is planned to install some additional 45 geophones.The study was carried out to identify some trends in seismicity as the mining goes deeper and to find thecorrelation with some main controlling parameters – volume and depth of the production in order to obtaininformation for future seismic hazard and risk analysis. Custom made applications within mXrap were utilisedto carry out the spatial variations of seismicity.The analysis showed substantial difference between the seismicity in the three studied blocks – 15/16, 28/30,and 33-37/34, with the weakest seismic activity in Block 15/16 (Mmax 1.6, maximum observed magnitude),followed by Block 28/30 (Mmax 2.2), and then largest seismicity in Block 33-37/34 (Mmax 2.2). The dailyseismicity rate increased substantially through the years only for Block 33-37/34. The seismicity correlatesstrongly with the production depth. In general a straightforward correlation between the production volumeand number of larger events (M > 0) was not found ...